Confucianism and Preferences: Evidence from Lab Experiments in Taiwan and China - Elaine M. Liu; Juanjuan Meng; Joseph Tao-yi Wang (Institute for the Study of Labor (IZA), 2013)
This paper investigates how Confucianism affects individual decision making in Taiwan and in China. We found that Chinese subjects in our experiments became less accepting of Confucian values, such that they became significantly more risk loving, less loss averse, and more impatient after being primed with Confucianism, whereas Taiwanese subjects became significantly less present-based and were inclined to be more trustworthy after being primed by Confucianism. Combining the evidence from the incentivized laboratory experiments and subjective survey measures, we found evidence that Chinese subjects and Taiwanese subjects reacted differently to Confucianism.
Keywords: C91; Z10; 330; social norm; Confucianism; time preferences; risk aversion; trust; Entscheidung; Verhaltensökonomik; Zeitpräferenz; Risikopräferenz; Konfuzianismus; Test; China; Taiwan